Pengaruh Revaluasi Asset Non Keuangan, Goodwill dan Goodwill-impairment Terhadap Biaya Audit dengan Kepemilikan Keluarga sebagai Variabel Moderasi - Sari, Sarlina (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2020)
The purposes of this study are to examine the effect of non-financial assets revaluation, goodwill and goodwill-impairment on audit fees family ownership as moderating variables. This research uses sample of Indonesia Stock Exchange non-financial companies from the years 2011-2015. Regression results show that revaluation of non-financial assets, goodwill and goodwill-impairment have no effect on audit fees. However, companies that family-owned, the audit fee is higher if the companies revalue its nonfinancial assets. The results of this study can be considered by regulators to set auditing standards related to audit of fair value that require complex accounting estimates, so that auditors are more aware abaout the reliability of fair values that are difficult to observe.Keywords: Non-financial assets revaluation; goodwill, goodwill-impairment; audit fees; family ownership